Recurso de comunicação aumentativa e alternativa: tecnologia assistiva de inclusão para o processo de ensino e aprendizagem de alunos autistas - Sousa, Siarla Danielle Andrade (2025)
This dissertation addresses the school inclusion of students with autism spectrum disorder (ASD), with an emphasis on Augmentative and Alternative Communication (AAC) resources as a strategy to foster teaching and learning. The choice of the topic stemmed from the need to understand how assistive technology can support teachers’ work and expand participation opportunities for autistic students, considering the reality of a public municipal school in Capitão de Campos, Piauí, Brazil. The main objective was to analyze how AAC resources contribute to pedagogical practice, broken down into the following objectives: to describe the use of assistive technology in the school context; to analyze the contributions of AAC to the development of social, cognitive, and academic skills; to identify teachers’ knowledge and perceptions regarding the use of these resources; and to develop a micro-certification course and an e-book to support teaching practice. A qualitative methodology was adopted, with an integrative literature review and field research, using a questionnaire, narrative interview, and participant observation. The study involved teachers from early childhood education and the initial years of elementary education, as well as support teachers at the school. The results revealed that the teachers recognize the importance of AAC in the learning process, particularly in stimulating communication and participation among children with ASD. On the other hand, they highlighted limitations regarding their knowledge of how to effectively integrate these resources into their daily practices, revealing the need for continuous training and technical- pedagogical support. It is concluded that investing in the strengthening of inclusive pedagogical practices requires not only access to resources but also support for teachers to use them meaningfully, thereby ensuring the right to education for all